Biological characterization and clinical significance of cuproptosis-related genes in lung adenocarcinoma - Meilin Li; Yu Tan; Zhixin Li; Lingfeng Min (BMC Pulmonary Medicine)
Abstract Background Lung cancer has high morbidity and mortality rates, which results in a poor prognosis. Cuproptosis is a novel cell death mechanism. The aim of this study was to examine the biological characteristics and clinical significance of genes associated with cuproptosis in lung adenocarcinoma (LUAD), and to understand the molecular mechanisms underlying the occurrence and progression of LUAD. Methods We targeted 10 cuproptosis-related genes from previous studies and used the datasets from GEO and TCGA databases to identify differential genes related to cuproptosis; then the data were analyzed by R package, Cytoscape, TISDB, cBioPortal, STRING, CancerSEA, and Disgenet; and finally, the data were detected by immunohistochemistry validation was performed. Results CDKN2A and MTF1 were cuproptosis-associated LUAD differential genes and were differentially expressed in immune subtypes. The expression of CDKN2A and MTF1 showed correlation with multiple functional states of LUAD.CDKN2A was negatively correlated with LUAD survival prognosis. Conclusion CDKN2A and MTF1 were correlated with the diagnosis of LUAD, and CDKN2A was negatively correlated with the survival and prognosis of LUAD. CDKN2A has the potential to contribute to the early diagnosis and prognosis analysis of LUAD.